Applying multifractal spectrum combined with fractal discrete brownian motion model to wood defects recognition for sawing - Lei Yu; Dawei Qi (2009 IEEE International Conference on Automation and Logistics, 2009)
Wood nondestructive testing technology is a new and comprehensive subject. In recent years it has achieved fast development. X-ray computed tomography (CT) scanning technology has been applied to the detection of internal defects in the logs for the purpose of obtaining prior information, which can be used to arrive at better wood sawing decision. Fractal geometry and its multifractal extension are new tools which can be used for describing, modeling, analyzing and processing different complex shapes and images. A method in CT image edge detection by using multifractal theory combined with fractal Brownian motion is applied in the paper. First its multifractal spectrum is estimated. Then different types of pixels are classified by the spectrum, smoothing edge point and singular edge point.